Using remote sensing and GIS for a hydro-meteorology based drought vulnerability map for farmers in Pitpitan, Bulakan, Bulacan - Sempio, Julius Noah H.
For agriculture to withstand the adverse effects of climate change and remain productive in spite of unusual weather phenomena, active adaptation is a practicable option for farmers and government agencies alike. Other strategies, such as theconstruction of water retention ponds and developing climate-adaptable varieties, require heavy funding that, without institutional support, are beyond the Filipino farmers' financial capabilities. Also, these strategies take many years to build and bear fruit. In view of these shortcomings and vulnerability to extreme weather events, immediate and low-cost adaptation measures are needed for farmers to consider while waiting for the long-term solutions. This paper presents the development of a methodology using remote sensing and GIS techniques in determining the vulnerability to climate irregularities of a farming community in Pitpitan, Bulakan, Bulacan. This methodology is intended to become part of a GIS-based climate adaptation recommender system that, in consideration of farmers' customary practices, will help to inform them of alternative adaptive measures in cases of imminent climate issues such as drought and floods. Search of related literature, personal visits to concerned local government units, and discussions with Pitpitan’s farmers reveal that, in general, farmers are more concerned with drought than with heavy flooding. Thus focus was given on helping farmers cope with drought conditions, and the developed methodology made use of a reduced version of the agricultural drought vulnerability index (ADVI), which is a data-intensive climatic vulnerability assessment index developed in India. ADVI is modified in order to take into account current data shortcomings of the Philippines, and still come up with a potentially useful analysis tool for extreme climate vulnerability of farm parcels in Pitpitan. The resulting thematic maps are then validated by farmers for being accurate and informative. A prototype table of recommendations was also developed with the reduced ADVI (rADVI) methodology, which aims to provide farmers with suggested adaptation measures based on their parcels' rADVI ranking and the expected rainfall situation in the Pitpitan area. These recommendations at parcel level were arrived at using GIS that incorporates both established agricultural strategies and local farmers' knowledge of time-tested strategies.